Fasting Blood Glucose with Serum Creatinine Levels in Type 2 Diabetes Mellitus Patients - Yohan Trayanus Lasarus Djaha; Maria Kurni Menga; Darmi Arda (Journal Interdisciplinary Health, 2026)
Introduction: Type 2 Diabetes Mellitus (T2DM) is a major global health problem associated with various chronic complications, particularly diabetic nephropathy. Persistent hyperglycemia can damage renal microvasculature and lead to impaired kidney function. Fasting blood glucose (FBG) is commonly used to assess glycemic control, while serum creatinine is a key indicator of renal function. Understanding the relationship between these parameters is important for early detection of kidney complications among patients with T2DM. This study aimed to analyze the relationship between fasting blood glucose levels and serum creatinine levels in patients with Type 2 Diabetes Mellitus in a primary healthcare setting. Research Methodology: This study employed an analytical observational design using a cross-sectional approach. Data were collected from medical records of patients with Type 2 Diabetes Mellitus at UPT Puskesmas Buki, Indonesia, in March 2026. A total of 38 patients who met the inclusion criteria were selected using purposive sampling. Fasting blood glucose levels were measured using the enzymatic GOD-PAP method, while serum creatinine levels were determined using the Jaffe reaction method. Data were analyzed using descriptive statistics and Spearman’s rank correlation test with a significance level of p ≤ 0.05. Results: The mean fasting blood glucose level was 176.4 ± 42.5 mg/dL, while the mean serum creatinine level was 1.18 ± 0.36 mg/dL. Statistical analysis revealed a moderate positive correlation between fasting blood glucose and serum creatinine levels (r = 0.421; p = 0.009). This indicates that higher fasting blood glucose levels tend to be associated with increased serum creatinine levels. Conclusions: Fasting blood glucose levels are significantly associated with serum creatinine levels among patients with Type 2 Diabetes Mellitus. Regular monitoring of glycemic status and renal function in primary healthcare settings is essential for early detection and prevention of diabetic kidney complications.